Glycation stimulates cutaneous monocyte differentiation in reconstructed skin in vitro. (March 2017) - Pageon, H.; Zucchi, H.; Rousset, F.; Girardeau-Hubert, S.; Tancrede, E.; Asselineau, D.
Highlights: Investigation of monocytes differentiation in reconstructed skin. AGES potentiate monocytic differentiation in reconstructed skin. Macrophages in skin from aged donors are correlated with the level of AGEs. Abstract: Glycation reaction is a recognized mechanism related to chronological aging. Previous investigations in cutaneous biology have considered the effect of glycation on the dermal matrix molecules, involved in tissue stiffening during skin aging. However, little is known about a possible direct effect of glycation upon cell differentiation. To address such issue, the effect of glycation has been re-investigated in a reconstructed skin model integrating monocytes that are cells capable of differentiating according to different pathways. The results showed that, in the absence of glycation, a small number of these CD45 + cells could differentiate either into dendritic-like cells (DC-SIGN +, BDC1a +, DC-LAMP + ) or macrophage- like cells (CD14 +, CD68 +, CD163 + ) whereas, with glycation, the number of monocytes, dendritic cells, macrophage-like cells were found surprisingly increased. In-vivo our results showed also that dendritic and macrophage-like cells were increased and suggest a possible link with the age-dependent glycation level in the skin. In addition, we found that, unlike fibroblasts incorporated in the reconstructed skin, these cells expressed specific receptors for AGEs (RAGE and SRA). Taken altogether, our data show that cells of the monocyte lineage, in the presence of AGEs, can differentiate into dendritic or macrophage-like cells and could lead to a micro inflammatory environment.